Virulence and Diversity of Wheat Leaf Rust in the United States in 1993 to 1995 - Long, D L (Plant disease, 1998)
Isolates of Puccinia triticina were obtained from wheat leaf collections made by cooperators throughout the United States and from cereal rust field surveys of the Great Plains, Ohio Valley, and Gulf Coast states in 1993, 1994, and 1995. Sixty-two virulence/avirulence phenotypes on 14 host lines that are near-isogenic for leaf rust resistance were found among 681 single uredinial isolates in 1993, 42 phenotypes were found among 683 isolates in 1994, and 51 among 701 isolates in 1995. As in previous surveys, regional race distribution patterns showed that the central United States is a single epidemiological unit distinct from the eastern United States. The distinctive racial composition of collections from the Southeast, Northeast, and Ohio Valley indicates that populations of P. triticina in those areas are discrete, suggesting epidemics originate from localized overwintering sources